The effect of combined fig-Walnut syrup on functional constipation in pregnant women: a randomized controlled trial - Roghayyeh Valizadeh; Sakineh Mohammad-Alizadeh-Charandabi; Khadijeh Hajizadeh; Mostafa Araj-Khodaei; Mojgan Mirghafourvand (Nutrition & Metabolism)
Abstract Background Constipation is one of the most common gastrointestinal complaints during pregnancy. Consuming fruits and vegetables is often the first line of treatment due to their fiber content. Therefore, the purpose of the present study was to determine the effect of combined fig-walnut syrup on functional constipation (FC) and quality of life (QoL) in pregnant women. Methods In this double-blind, randomized controlled clinical trial, 90 pregnant women with FC were randomly assigned to receive combined fig-walnut syrup, fig syrup, or placebo (n = 30 in each group) using block randomization. Participants received 15 ml of syrup once daily at night, half an hour before bedtime, for 14 days and were followed up for 2 weeks after the end of the intervention. The FC, quality of life-gravidity (QOL-GRAV), and food frequency questionnaires (FFQ) were used to collect data. The questionnaires were completed once before the intervention and then the FC questionnaire was completed once a week for four weeks and the QoL questionnaire was completed at the end of the fourth week. To compare the outcomes among the study groups, one-way AONOVA, ANCOVA, Mann- Whitney U test, and Kruskal- Wallis test were used. Results Following the intervention, although there was no statistically significant difference in the number of defecations between the combined fig-walnut syrup group and the fig syrup group (P > 0.05) at every four weeks, there was a statistically significant difference compared to the placebo (P < 0.05). Combined fig-walnut syrup (adjusted mean difference (AMD): -3.4; 95% confidence interval: -0.7 to -6.1; P = 0.008) and fig syrup (AMD: -5.8; 95% CI: -3.1 to -8.6; P < 0.001) improved QoL compared to the placebo group and there was no statistically significant difference between the combined fig-walnut and fig syrup (AMD: 2.4; 95% CI: 5.2 to -0.3; P = 0.104). Conclusion The consumption of fig-walnut syrup and fig syrup may help improve constipation symptoms and enhance QoL during pregnancy. Further studies are needed to reach a conclusive determination. Trial registration Iranian Registry of Clinical Trials (IRCT): IRCT2012071801032N79. Date of registration: 07.12.2023.